Niobium Nanowire Yarns and their Application as Artificial Muscles. (5th April 2013) - Mirvakili, Seyed M.; Pazukha, Alexey; Sikkema, William; Sinclair, Chad W.; Spinks, Geoffrey M.; Baughman, Ray H.; Madden, John D. W.
Abstract Metal nanowires are twisted to form yarns that are strong (0.4 to 1.1 GPa), pliable, and more conductive (3 × 106 S m−1) than carbon nanotube yarns. Niobium nanowire fibers are extracted by etching a copper‐niobium nano‐composite material fabricated using the severe plastic deformation process. When impregnated with paraffin wax, the niobium (Nb) nanowire yarns produce fast rotational actuation as the wax is heated. The heated wax expands, untwisting the yarn, which then re‐twists upon cooling. Normalized to yarn length, 12 deg mm−1 of torsional rotation was achieved along with twist rates in excess of 1800 rpm. Tensile modulus of 19 ± 5 GPa was measured for the Nb yarns, which is very similar to those of carbon multiwalled nanotubes.